Advancing Roles of Healthcare Professionals in Palliative Radiotherapy. Issue 11 (November 2020) - Fitzpatrick, C.; Javor, J.; Zywine, C.; Job, M.; Gram, V.
Abstract: New methods of working in relation to the management of patients requiring palliative radiotherapy are being embraced in hospital departments around the world. Team members are expanding on their previously assigned scope of practice to take on duties that had previously only been assigned to a consultant clinical oncologist. Career frameworks such as the four-tier model have been built upon to identify the skills held by other healthcare professionals and show how they may be best placed to take on additional roles within a patient pathway. Experiences of four departments in different countries report their local experiences in using both therapeutic radiographers and nursing staff to undertake advanced and consultant-level practice in relation to the management of both palliative radiotherapy patients and their research work streams. Involvement of other healthcare professionals within the clinical or research pathway for the management of palliative radiotherapy patients can be achieved. Their involvement can support clinicians and help to ensure the safe and efficient management of patients requiring palliative radiotherapy.